Pengaruh Kecemasan Matematika Terhadap Kemampuan Pemahaman Konsep Matematis Siswa di Kelas VII SMP Negeri 4 Bukittinggi - Khairat, Yudrikhul; Firmanti, Pipit; Rusdi, Rusdi; Fitri, Haida (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research is motivated by the low mathematics learning outcomes of students. This math anxiety can be an obstacle for a person to be able to understand math. This study aims to determine the influence of mathematical anxiety on the ability to understand mathematical concepts of grade VII students of SMP Negeri 4 Bukittinggi. This type of research is correlational research. The population in this study is all grade VII students totaling 304 students of SMP N 4 Bukittinggi. While the sample in this study is class VII.A. The sampling technique is carried out randomly using cluster random sampling. The instruments used in this study are mathematical anxiety questionnaires and mathematical concept comprehension ability test questions. The data analysis technique used is simple linear regression. The results of the study can be concluded that there is an influence of mathematical anxiety on the ability to understand mathematical concepts of students in grade VII of SMP N Bukittinggi. This can be seen from the linear regression equation, which is Y = 30.014 - 0.209X from the result, mathematical anxiety has a negative effect on the ability to understand mathematical concepts